Hysteresis for solving nonlinear problem for an elastic beam structures - Шамровский, А. Д.; Миняйло, Т. А. (Eastern-European Journal of Enterprise Technologies, 2012)
The method of successive approximations is developed and applied. The solution of nonlinear problems for elastic beam structures based on this method is considered. The hysteresis phenomenon is investigated